Trend hijrah di kalangan remaja muslim milenial: Studi kasus mahasiswa pada Fakultas Sains dan Teknologi UIN Alauddin Makassar - Hastuti Hastuti; Rofia Masrifah; Titi Mildawati (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2020)
This research discussed about trend Hijrah in Among Teens Muslim Millineal (Study Case of Students of the faculty of Science and Technology UIN Alauddin Makassar). There are several subproblems which will be discussed in the research is the first, how the understanding of students abot the meaning of hijrah?, second, how are the factorsÂ causing the studentâ€™s migration? Third, how the factors inhibiting andÂ supporting the migration of students? Fourth, how solution to the migration of studenst so that the changes brought goodness? To answer the problem of the research is using the method of interview, observation or observation online using the questionnaire with google form and examines literature-literature science that relates to the discussion of this research. The work write ilmiah also an investigation of a systemic, controlled, empirical, and critical of the phenomenon-natural phenomenon guided by theories about the phenomena of the so phenomenological also one of the approaches that are used in this research. The phenomenon of migration in the teenage Muslim millineal be a concern for all people, the majority of people look at that trend moved in among teens is just as fashion as to follow the development of the times, a view this may mean that the people who seem to move (appearance) is only limited to the bandwagon.Penelitian ini membahas tentang Trend Hijrah di Kalangan Remaja Muslim Milineal (Studi Kasus Mahasiswa Fakultas Sains dan Teknologi UIN Alauddin Makassar). Ada beberapa submasalah yang akan dibahas dalam penelitian ini yang pertama, Bagaimana pemahaman mahasiswa tentang makna Hijrah? Kedua, faktor penyebab hijrahnya mahasiswa? Ketiga, Bagaimana solusi terhadap hijrahnya mahasiswa sehingga perubahan membawa kebaikan? Untuk menjawab masalah tersebut proposal penelitian ini menggunakan metode interviw, observasi atau pengamatan dan menggunakan kuisioner dengan google form serta menelaah literatur-literatur ilmiah yang berkaitan dengan pembahasan penelitian ini. Karya tulis ilmiah juga merupakan penyelidikan yang sistematis, terkontrol, empiris, dan kritis tentang fenomena-fenomena alami dengan dipandu oleh teori-teori tentang fenomena-fenomena tersebut sehingga fenomenologis juga salah satu pendekatan yang digunakan dalam penelitian ini. Fenomena hijrah di kalangan remaja muslim milineal menjadi perhatian bagi semua orang, sebagian orang memandang bahwa trend hijrah di kalangan remaja hanyalah sebagai fashion karena mengikuti perkembangan zaman, pandangan ini dapat diartikan bahwa orang yang kelihatan hijrah (penampilan) hanya sebatas ikut-ikutan.